International Conference on Smart Infrastructure and Construction 2019 (ICSIC) : driving data-informed decision-making - DeJong, M. J.; Schooling, J. M.; Viggiani, G. M. B. (ICE Publishing, 2019)
The International Conference on Smart Infrastructure and Construction 2019 (ICSIC) brings together world-leading academics and practitioners from the fields of infrastructure planning, asset management and sensing. The papers included in these proceedings cover a wide range of topics relevant to smart infrastructure and construction including material on cities, structures, geotechnical capabilities and digital solutions. Contributions have been supplied by academics and professionals working to develop smart solutions for design, delivery, operation and management of major infrastructure assets.